Direct international jurisdiction in Private International Law with special reference to article 57 of law No. 19.920 - Ferreira, Alejandro (2022)
The regulation of international private situations involves the determination of three empirical aspects. The substantive law applicable to the case, the courts that will have jurisdiction and the rules of legal continuity of judgments and arbitral awards, as well as the various mechanisms of international civil for criminal procedural cooperation. In this paper we will analyze the new bases of international jurisdiction determined in Law No. 19.920, as they represented a substantive transformation of the international legal landscape. The repeal of the Appendix to the Civil Code, especially article 2401 (which contained two criteria of bilateral jurisdiction), brought with it almost twenty criteria of direct jurisdiction, where party autonomy and forum of necessity stand out, among many other parameters without direct antecedents in the pre-existing Private International Law system of conventional and autonomous source. In this paper we address the new bases of jurisdiction and the limits provided in the light of General International Law.